C. 60%
The probability that a person surveyed is 40 or older and gets the news by reading the paper is 60%.
Step-by-step explanation:
In our case, we have to find the probability of a person getting their news by reading the paper. But we are given with a condition that the person must be 40 or older.
The survey is conducted among 80 people.
Number of people aged 40 or older = 40
No of people aged 40 or older and read paper = 24
Probability formula is the ratio of number of favorable outcomes to the total number of possible outcomes.
Probability of a person aged 40 or older reads a paper =
(No. of People aged 40 or older and read paper)/(No. of people aged 40 or older)
= 24/40
= 0.6
= 60%
Learn more about probability from brainly.com/question/10694003
#learnwithBrainly
see the attached figure with the letters
1) find m(x) in the interval A,BA (0,100) B(50,40) -------------- > p=(y2-y1(/(x2-x1)=(40-100)/(50-0)=-6/5
m=px+b---------- > 100=(-6/5)*0 +b------------- > b=100
mAB=(-6/5)x+100
2) find m(x) in the interval B,CB(50,40) C(100,100) -------------- > p=(y2-y1(/(x2-x1)=(100-40)/(100-50)=6/5
m=px+b---------- > 40=(6/5)*50 +b------------- > b=-20
mBC=(6/5)x-20
3)
find n(x) in the interval A,BA (0,0) B(50,60) -------------- > p=(y2-y1(/(x2-x1)=(60)/(50)=6/5
n=px+b---------- > 0=(6/5)*0 +b------------- > b=0
nAB=(6/5)x
4) find n(x) in the interval B,CB(50,60) C(100,90) -------------- > p=(y2-y1(/(x2-x1)=(90-60)/(100-50)=3/5
n=px+b---------- > 60=(3/5)*50 +b------------- > b=30
nBC=(3/5)x+30
5) find h(x) = n(m(x)) in the interval A,B
mAB=(-6/5)x+100
nAB=(6/5)x
then
n(m(x))=(6/5)*[(-6/5)x+100]=(-36/25)x+120
h(x)=(-36/25)x+120
find <span>h'(x)
</span>h'(x)=-36/25=-1.44
6) find h(x) = n(m(x)) in the interval B,C
mBC=(6/5)x-20
nBC=(3/5)x+30
then
n(m(x))=(3/5)*[(6/5)x-20]+30 =(18/25)x-12+30=(18/25)x+18
h(x)=(18/25)x+18
find h'(x)
h'(x)=18/25=0.72
for the interval (A,B) h'(x)=-1.44
for the interval (B,C) h'(x)= 0.72
<span> h'(x) = 1.44 ------------ > not exist</span>
its none of them? 6y - 10/5 +7y = 12 10 divided by 5 equals 2
it will now look like this: 6y - 2 + 7y = 12
then your going to want to add 2 to both sides of the equation.
it will now look like this: 6y -2 + 7y + 2 = 12 + 2 = 14
simplify: 6y + 7y = 14
add the like terms: 13y = 14